Mechanistic insights into acid-catalysed pyrolysis of cellulose and its model compounds - Long, Yu (Curtin University, 2022)
Biomass has only been utilised as an energy source via direct combustion of bio-charcoal in the past decade, but the biomass processes also create environmental issues and low energy utilization. This study provides new insights into cellulose pyrolysis mechanisms for the benefit of advanced bio-oil and bio-product selectivity technologies and maximise the utilisation of the biomass in the future green energy market, which can effectively reduce the green house emission and its environmental issue.